Trust in Food - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (Encyclopedia of Food and Agricultural Ethics, 2019)
Trust is important in the food sector. This is primarily because households entrust some of the tasks related to food preparation to food processors. The public is concerned about pesticides, food additives, preservatives, and processed foods that may harbor unwanted chemicals or additives. After numerous food scandals, consumers expect food processing industries and retailers to take responsibility for food safety. Meanwhile, the food industry focuses on profit growth and costs reduction to achieve higher production efficiency and competitiveness. It means that they introduce innovations, such as new production methods, processing techniques, and additives. Consumers have to delegate the responsibility for ensuring food safety to food producers, retailers, and regulatory authorities who ensure that the foods are safe, healthy, and pose no risks. For consumers, trusting these actors can reduce feelings of uncertainty. It is helpful for companies to be responsible for their activities through transparency and traceability. In turn, the food industry tries to gain consumers' trust by providing objective information, such as ranked brands or labels on food packages.
Keywords: P46; D18; L66; O18; 330; Consumer confidence; Food scares; Food risk; Food safety